Cataract surgery and age-related macular degeneration. Issue 1 (January 2017) - Ehmann, David S.; Ho, Allen C.
Abstract : Purpose of review: The following review describes the recent evidence regarding the effect of cataract surgery on age-related macular degeneration (AMD). Recent findings: For patients with both visually significant cataracts and AMD, recent evidence supports the role of cataract surgery with reports demonstrating improved visual acuity, absence of significant disease progression, and improved quality of life. Summary: Recent evidence does not find cataract surgery to cause or worsen AMD.